Phylogenetic relationships of chemoautotrophic bacterial symbionts of Solemya velum say (Mollusca: Bivalvia) determined by 16S rRNA gene sequence analysis. - Eisen, J A (1992)
The protobranch bivalve Solemya velum Say (Mollusca: Bivalvia) houses chemoautotrophic symbionts intracellularly within its gills. These symbionts were characterized through sequencing of polymerase chain reaction-amplified 16S rRNA coding regions and hybridization of an Escherichia coli gene probe to S. velum genomic DNA restriction fragments. The symbionts appeared to have only one copy of the 16S rRNA gene. The lack of variability in the 16S sequence and hybridization patterns within and between individual S. velum organisms suggested that one species of symbiont is dominant within and specific for this host species. Phylogenetic analysis of the 16S sequences of the symbionts indicates that they lie within the chemoautotrophic cluster of the gamma subdivision of the eubacterial group Proteobacteria.